Influence of leucosapphire tubes growing conditions on strength of insulators made of the tubes - Vybyvanets, V.I.; Bochkov, N.A.; Konarev, S.A.; Kravetsky, D.Ya.; Sokolov, V.A.; Tsetskhladze, D.L. (Functional Materials, 2013)
The influence of leucosapphire tubes growing conditions (grades of molybdenum used for form-builders; raw materials brands; rates of growing; designs of form-builders and a growing tube shielding) on strength of the insulators made of the tubes have been studied.